The Role of teacher in medical student self-directed learning process - Francisca A Tjakradidjaja; Yayi Suryo Prabandari; Titi Savitri Prihatiningsih; Harsono Harsono (Journal of Education and Learning (EduLearn), 2016)
Self-directed learning (SDL) is essential in medical education. The rapid development of medical science and the expansion of health problems need a physician who can meet that challenges. A physician must have lifelong learning ability. SDL is one of the important requirements for lifelong learning ability. In SDL, learners are the controller of learning and learners have the freedom to learn according to their needs. Therefore, it is necessary to explore the role of the teacher in the SDL process, particularly in medical education. This study used a qualitative exploratory design. Twelve teachers and 23 medical students were selected by purposive sampling. There were seven themes that emerged from the analysis. The role of teacher in the SDL process includes: (1) Competent; (2) Concern; (3) Creative; (4) Facilitator; (5) Motivator; (6) Partners; and (7) Role Model.